Cover Feature: In Silico Evidence That Protein Unfolding is a Precursor of Protein Aggregation (ChemPhysChem 5/2020). Issue 5 (4th March 2020) - Bianco, Valentino; Franzese, Giancarlo; Coluzza, Ivan
Abstract : The Cover Feature illustrates partial unfolding of the native conformation and ultimately complete loss of the folded structures and formation of protein aggregates resulting from increasing the protein concentration in an aqueous environment. The water mediates the partial unfolding with no direct protein‐protein interactions. More information can be found in the Article by V. Bianco et al. on page 377 in Issue 5, 2020 (DOI: 10.1002/cphc.201900904 ).